Changes of Serum Calcium, Magnesium and Parathyroid Hormone Induced by Hemodialysis with Citrate-Enriched Dialysis Solution - Roman Šafránek; Petr Moučka; Jaroslava Vávrová; Vladimír Palička; Ladislava Pavlíková; Sylvie Dusilová Sulková (Karger Publishers, 2015)
Background/Aims: In recent years, one of technical attempts to improve biocompatibility and tolerability of the hemodialysis procedure is the substitution of acetate in dialysis solution with citrate. The aim of our study was to compare two dialysis solutions: traditional bicarbonate dialysis solution containing acetate (3 mmol/L) (solution A); and (solution C) commercially produced citrate-enriched bicarbonate dialysis solution (0.8 mmol/L citrate). Methods: Patients from a single hemodialysis center (N=126) were included in the study. Both conventional low-flux hemodialysis and on-line hemodiafiltration procedures were studied. Both dialysis solutions contained identical calcium (1.5 mmol/L) and magnesium (0.5 mmol/L) concentrations. Results: Parathyroid hormone (iPTH) concentration decreased during procedures with solution A by 64%. On the contrary, when solution C was used, iPTH concentration increased insignificantly by 4%. For solution A, serum calcium and magnesium increased during procedures in patients with predialysis concentrations lower than 2.33 and 0.76 mmol/L, respectively. In procedures with dialysis solution C these concentrations were significantly lower: 2.19 mmol/L for Ca and 0.68 mmol/L for Mg. Conclusion: Our study clearly shows that the substitution of part of acetate with citrate in dialysis solution significantly influences changes of serum calcium, magnesium and parathyroid hormone concentrations during hemodialysis and hemodiafiltration procedures.